Bicentennial in Peru in the context of the global crisis due to the pandemic (2020-2021) - Llanos Argumanis, Ernesto Walter (2022)
This essay attempts to make a critical reflection on the Bicentennial of Peru (1821-2021) in the context of the global crisis due to the COVID-19 pandemic (2020-2021); above all, in reference to the democratic fragility in Peru as a result of the successive coups d’état during its republican history and the recent political crises. The polarized confrontation of the political dynamics, the lack of dialogue, corruption, media sensationalism, citizen indignation and indifference and the lack of addressing the problems of injustice and social inclusion show political ineffectiveness, characterized by conservatism, authoritarianism, corruption and power struggles that ignore the interests of a fragmented nation with a democratic political culture in a precarious and eventful formation process.